A comparison of cardinal tournaments and piece rate contracts with liquidity constrained agents - MARINAKIS, Kosmas (Institutional Knowledge at Singapore Management University, 2012)
Acelebrated result in the theory of tournaments is that relative performance evaluation (tournaments) is a superior compensation method to absolute performance evaluation (piece rate contracts) when the agents are risk-averse, the principal is risk-neutral or less risk-averse than the agents and production is subject to common shocks that are large relative to the idiosyncratic shocks. This is because tournaments get closer to the first best by filtering common uncertainty. This paper shows that, surprisingly, tournaments are superior even when agents are liquidity constrained so that transfers to them cannot fall short of a predetermined level. The rationale is that, by providing insurance against common shocks through a tournament, payments to the agents in unfavorable states increase and payments in favorable states decrease which enables the principal to satisfy tight liquidity constraints for the agents without paying any ex ante rents to them, while simultaneously providing higher-power incentives than under piece rates. The policy implication of our analysis is that firms should adopt relative performance evaluation over absolute performance evaluation regardless of whether the agents are liquidity (wealth) constrained or not.